Total Factor Productivity (TFP) and its Differentiation in the European Union Member States - Młynarzewska-Borowiec, Izabela Ewa (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Total Factor Productivity (TFP) is the synthetic measure of effectiveness of the production process in a country due to technological progress. The aim of the article is to examine (with the use of econometric methods) the level and dynamics of TFP in the particular European Union member states in the period 2000–2014 and to point out the direction of TFP changes in the analysed group of countries. In the article one makes the attempt to answer the question whether the productivity convergence, influencing relevantly the real convergence process in the EU, is also possible.